Near-source wastewater surveillance as a non-invasive tool for disease detection in prisons - O’Mara, Oscar; Hassard, Francis; Jobling, Kelly; Quintela-Baluja, Marcos; McIntyre-Nolan, Shannon; Lundy, Lian; Singer, Andrew C.; Rahimzadeh, Shadi; Stanton, Isobel; Castro-Gutierrez, Victor; Charlotte-Smith, Hannah; Vu, Milan; et al. (Springer, 2026)
Near-source wastewater-based epidemiology (WBE) offers a non-intrusive alternative to clinical testing of whole prison populations. Prisons sit at the centre of high transmission risk but experience limited health-care access and barriers to testing individual prisoners. However, the use of WBE for health protection in prison settings has been limited. To assess its merit during the COVID-19 pandemic, SARS-CoV-2 RNA concentrations were quantified in 680 composite wastewater samples collected from 14 prisons across England and Wales between January and June 2021. Viral RNA was detected in 48% of samples, and wastewater viral loads were found to closely mirror clinical case numbers Lead–lag analysis with adjacent municipal wastewater samples indicated a bidirectional flow between the prisons and their local community: seven prisons exhibited wastewater peaks ahead of their communities, while six lagged, highlighting heterogeneous epidemiological coupling. Marked differences between prisons were apparent in both physicochemical wastewater traits and clinical testing uptake, indicating each institution constitutes a distinct surveillance unit. Collectively, findings here indicate near-source WBE as a rapid, unbiased and scalable tool for disease outbreak detection and for mapping disease flow between prisons and their surrounding communities, advocating its integration into routine health-security frameworks for custodial and other high-density settings.
Keywords: 48 Law and Legal Studies; 4402 Criminology; 44 Human Society; Infectious Diseases; Clinical Research; Social Determinants of Health; Coronaviruses; Health Disparities; Emerging Infectious Diseases; Health Disparities and Racial or Ethnic Minority Health Research; Coronaviruses Disparities and At-Risk Populations; Infection; 3 Good Health and Well Being; Diseases; Environmental sciences; NATURAL SCIENCES::Biology::Organism biology::Microbiology